FINANCIAL MARKET SPECULATIVE TRANSACTIONS - K. E. Маnuylov (Vestnik MGIMO-Universiteta)
The article highlights the transformation of financial market, which determines its insulation as an independent economy sector. The tendency was first analyzed in late XIX century and has been developing since then, resulting in dissociation of real and financial sectors. Due to uncertainty traders lack decision guidelines, as speculative transactions do not imply property management. As a result, their decisions are based on expectations and market value losses any connection to real sector performance. Financial derivatives development through late XX century has brought financial market independence to a new level and inflation of the sector to values, exceeding world GDP. Stock market has provided the basis for property and management separation, and derivatives, in turn, separate returns from property and risk from asset. As risk valuation turns out to be the measure of market expectations, it is sure to affect the basic asset prices even more than underlying real capital. The imbalance is believed to have been one of the determinants of the modern financial and economic crisis. Financial market has evidently transformed to a casino to a greater extent, than Keynes identified.